Dosimetry analyses comparing high-dose-rate brachytherapy, administered as monotherapy for localized prostate cancer, with stereotactic body radiation therapy simulated using CyberKnife. (23rd June 2014) - Fukuda, Shoichi; Seo, Yuji; Shiomi, Hiroya; Yamada, Yuji; Ogata, Toshiyuki; Morimoto, Masahiro; Konishi, Koji; Yoshioka, Yasuo; Ogawa, Kazuhiko
Abstract : The purpose of this study was to perform dosimetry analyses comparing high-dose-rate brachytherapy (HDR-BT) with simulated stereotactic body radiotherapy (SBRT). We selected six consecutive patients treated with HDR-BT monotherapy in 2010, and a CyberKnife SBRT plan was simulated for each patient using computed tomography images and the contouring set used in the HDR-BT plan for the actual treatment, but adding appropriate planning target volume (PTV) margins for SBRT. Then, dosimetric profiles for PTVs of the rectum, bladder and urethra were compared between the two modalities. The SBRT plan was more homogenous and provided lower dose concentration but better coverage for the PTV. The maximum doses in the rectum were higher in the HDR-BT plans. However, the HDR-BT plan provided a sharper dose fall-off around the PTV, resulting in a significant and considerable difference in volume sparing of the rectum with the appropriate PTV margins added for SBRT. While the rectum D5cm 3 for HDR-BT and SBRT was 30.7 and 38.3 Gy ( P < 0.01) and V40 was 16.3 and 20.8 cm 3 ( P < 0.01), respectively, SBRT was significantly superior in almost all dosimetric profiles for the bladder and urethra. These results suggest that SBRT as an alternative to HDR-BT in hypofractionated radiotherapy for prostate cancer might have an advantage for bladder and urethra dose sparing, but for the rectum only when proper PTV margins for SBRT are adopted.